Bosnia and Herzegovina : 2010 Article IV Consultation Second and Third Reviews Under the Stand-By Arrangement Request for Waiver of Nonobservance of a Performance Criterion and Rephasing of Purchases. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The global economic and financial crisis found the economy of Bosnia and Herzegovina in a vulnerable position. The government put together a comprehensive program supported by the International Monetary Fund. The stabilization program has helped mitigate the impact of the global financial crisis on the economy. With the economy now emerging out of the recession, policy continuity is important. Medium-term fiscal consolidation should be accompanied by reforms in current spending while making room for capital expenditure. The response in the financial sector has been appropriate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet